Efektivitas Pemanfaatan Limbah Kertas Sebagai Bahan Tambahan Pembuatan Batako - Barus, Linda; Masra, Ferizal; Indarwati, Suami (MIDWIFERY JOURNAL, 2025)
Background: Paper waste contributes approximately 10% of the total national waste in Indonesia. Improper management leads to accumulation in landfills and the production of methane gas. Utilizing paper waste as an additional material in brick manufacturing offers an environmentally friendly innovation that may reduce waste generation and provide more sustainable building materials.Purpose: This study aims to analyze the effect of various paper waste compositions on the compressive strength and water absorption of concrete bricks and to determine the most optimal composition based on SNI 03-0349-1989.Methods: This experimental study used paper waste compositions of 0%, 15%, 20%, and 25%. A total of 30 brick samples were tested. Compressive strength was measured using a Universal Testing Machine (UTM) at 28 days, while water absorption was tested through a 24-hour immersion process. Data were analyzed using ANOVA and Pearson correlation.Results: The findings show that higher paper waste content decreases compressive strength, indicated by a strong negative correlation (r = –0.72). The 0% and 15% variations met SNI standards for Grade I–II, while the 20% and 25% variations met Grade III–IV. Water absorption values for all variations were below 1%, fulfilling SNI requirements (maximum 25%). The 15% composition was identified as the most optimal variation. Conclusion: Paper waste significantly reduces compressive strength but does not negatively affect water absorption. A 15% composition is recommended because it meets SNI standards while supporting waste reduction efforts.Suggestion: Paper waste usage should be limited to a maximum of 15% for non-structural construction. Further studies may incorporate additives such as lime or fly ash to improve brick performance. Local governments and small industries are encouraged to adopt this innovation to reduce paper waste generation. Keywords: Paper Waste, Compressive Strength, Water Absorption, Concrete Brick  Latar Belakang: Sampah kertas menyumbang sekitar 10% dari total timbulan sampah nasional di Indonesia. Pengelolaan yang kurang optimal menyebabkan penumpukan di TPA dan menghasilkan gas metana. Pemanfaatan limbah kertas sebagai bahan tambahan pembuatan batako menjadi inovasi ramah lingkungan yang berpotensi mengurangi timbulan sampah serta menyediakan bahan bangunan yang lebih berkelanjutan. Tujuan: Penelitian ini bertujuan untuk mengetahui pengaruh variasi komposisi limbah kertas terhadap kuat tekan dan daya serap air batako serta menentukan komposisi paling optimal berdasarkan SNI 03-0349-1989.Metode: Penelitian eksperimen ini menggunakan variasi campuran limbah kertas 0%, 15%, 20%, dan 25%. Total 30 sampel batako diuji. Kuat tekan diukur menggunakan Universal Testing Machine (UTM) pada umur 28 hari, sedangkan daya serap air diuji melalui metode perendaman 24 jam. Data dianalisis dengan uji ANOVA dan korelasi Pearson.Hasil: Hasil penelitian menunjukkan bahwa semakin tinggi persentase limbah kertas maka semakin rendah kuat tekan batako, ditunjukkan oleh korelasi negatif kuat (r = –0,72). Variasi 0% dan 15% memenuhi SNI Mutu I–II, sementara 20% dan 25% hanya memenuhi Mutu III–IV. Semua variasi memiliki daya serap air di bawah 1%, sehingga memenuhi standar SNI (maksimal 25%). Komposisi paling optimal adalah 15%.Kesimpulan: Limbah kertas berpengaruh signifikan terhadap penurunan kuat tekan batako namun tidak menurunkan kelayakan daya serap air. Komposisi 15% direkomendasikan karena masih memenuhi standar SNI sekaligus mengurangi penggunaan bahan baku mineral.Saran: Penggunaan limbah kertas direkomendasikan maksimal 15% untuk konstruksi non-struktural. Penelitian lanjutan dapat menambahkan bahan additive seperti kapur atau fly ash untuk meningkatkan kualitas batako. Pemerintah daerah dan industri kecil disarankan mengadopsi inovasi ini guna mengurangi timbulan sampah kertas. KataKunci: Limbah Kertas, Kuat Tekan, Daya Serap Air, Batako